Emotional Intelligence and Work-related Stress among Nurses Working in Psychiatric Hospitals (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Emotional Intelligence is a broad concept that connecting various personality and cognitive traits of human beings. The concept of emotional intelligence is described as the individual’s capability of recognizing their own emotions and the emotions of others, and practice this understanding to navigate important interactions successfully. Aims: The purpose of this study is to assess emotional intelligence among nurses working in psychiatric hospitals, as well as the relationship between emotional intelligence and workplace stress. Methodology: A descriptive correlational study design using a convenience sample of (N=109) nurses working in two main psychiatric hospitals. Two separated scales (The Emotional Intelligence Scale-34 items and The Work-related Stress scale-24 items) was used to meet the study objectives. Results: The study findings indicate that emotional intelligence levels were ranged between moderate to high among study participants. However, the majority had moderate work-related stress about (61%). Nurses’ work stress was found to have significant relationship with their emotional intelligent level. Conclusion and Recommendations: Despite the positive levels of emotional intelligence nurse have, working in psychiatric hospitals is still cause of stress for nurses. The statistical relationship found in this study highlights the importance of enhancing emotional intelligence among nurses working in psychiatric hospitals settings by engaging them in effective training programs to maximize their abilities of adjustment and reduce their levels of work-stress.
Keywords: Emotional Intelligence, Work-related Stress, Psychiatric Nurses